PESAN MORAL SYAIR TRADISI RENTAK KUDO KECAMATAN HAMPARAN RAWANG (KAJIAN ANALISIS ISI) - Lolika Rahayu; Abdoel Gafar; Uli Wahyuni (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the moral message in the poetry of the Rentak Kudo tradition, Hamparan Rawang District. This research is based on the researcher's desire as a regional woman who wants to preserve her own regional culture. Apart from that, this research is a final assignment in the field of science that the researcher is currently working on. To carry out this research, the method the researcher used was qualitative descriptive research. This type of research can describe the moral messages contained in this traditional poetry. The data for this research was obtained directly from the poetry poet Rentak Kudo as the main data that will be analyzed from a review of the moral message. The results of this research describe that there is a moral message about human relations with fellow human beings which includes the affection aspect with 15 quotation data, the willingness to sacrifice aspect with 9 quotation data, the kinship aspect with 17 quotation data, the caring aspect with 31 quotation data, the deliberation aspect with 19 quotations. quotation data, aspects of mutual cooperation as much as 3 data quotations and helping each other as much as 5 data quotations. Thus, there are 99 moral messages about human relations with fellow humans in this traditional poetry. Poetry that contains a moral message about human relations with other humans will be easily remembered as a moral guide for listeners of the poetry.